In Vitro and In Silico Antioxidant Efficiency of Bio-Potent Secondary Metabolites From Different Taxa of Black Seed-Producing Plants and Their Derived Mycoendophytes - Hassane, Abdallah M. A.; Hussien, Saleh M.; Abouelela, Mohamed E.; Taha, Taher M.; Awad, Mohamed F.; Mohamed, Hassan; Hassan, Mohammad M.; Hassan, Mohammad H. A.; Abo-Dahab, Nageh F.; El-Shanawany, Abdel-Rehim A. (Frontiers in Bioengineering and Biotechnology, 2022)
Oxidative stress has been involved in the pathophysiology of multiple health complications, and it has become a major focus in targeted research fields. As known, black seeds rich sources of bio-active compounds and widely used for human health due to excellent medicinal and pharmaceutical properties. The present study aimed to investigate the antioxidant potency of the various black seeds and their derived mycoendophytes, determination of the total phenolic and flavonoid contents in different extracts, followed by characterization of major constituents by HPLC analysis, and finally in silico docking study to determine their binding affinities to target myeloperoxidase enzyme. Ten dominant mycoendophytes were isolated from different black seed plants, three isolates among them were selected based on high antiradical potency and further identified by performing the ITS ribosomal gene sequencing, and these isolated were Aspergillus niger TU 62, Chaetomium madrasense AUMC14830, and Rhizopus oryzae AUMC14823. Significant positive correlations were shown between total phenolics, flavonoids, and antioxidant activities of different tested extracts. The n-butanol extracts of both black seeds and their derived mycoendophytes showed reasonable IC50 values (0.81-1.44 mg/mL) compared to control with significant correlations among their phytochemical contents. Overall, seventeen standard phenolics and flavonoids were used and the compounds were detected in different degrees of existence and concentration in the examined extracts using HPLC analysis. Moreover, the investigation of molecular simulation results of detected compounds against myeloperoxidase enzyme revealed that, rutin as an targeted antioxidant possessed a high affinity (-15.3184 kcal/mol) as an inhibitor. Taken together, the black seeds and their derived mycoendophytes are promising candidates as bio-prospects for the broad industrial sector of antioxidants with several valuable pharmaceutical and nutritional potential applications.